2018
DOI: 10.18632/oncotarget.24084
|View full text |Cite
|
Sign up to set email alerts
|

In vitro, in vivo and ex vivo demonstration of the antitumoral role of hypocretin-1/orexin-A and almorexant in pancreatic ductal adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is still the poorest prognostic tumor of the digestive system. We investigated the antitumoral role of orexin-A and almorexant in PDAC. We analyzed the orexin receptor type 1 (OX1R) expression by immunohistochemistry in human normal pancreas, PDAC and its precursor dysplastic intraepithelial lesions. We used PDAC-derived cell lines and fresh tissue slices to study the apoptotic role of hypocretin-1/orexin-A and almorexant in vitro and ex vivo. We analyzed in vivo the hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
80
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(88 citation statements)
references
References 35 publications
7
80
0
1
Order By: Relevance
“…It should be noted that OX1R was not expressed in normal pancreas (acini and ducts) except in the Langerhans islets (Figure 3A ) in which orexins could play a role in insulin secretion ( 8 ). This expression in tumoral tissue was independent of patient age, gender, tumor size, and lymph node metastasis ( 46 ). The use of AsPC-1 cell line derived from human PDAC revealed that OxA was able to strongly inhibit cell growth by the SHP2-induced apoptosis ( 46 ).…”
Section: Pancreas Cancermentioning
confidence: 98%
See 4 more Smart Citations
“…It should be noted that OX1R was not expressed in normal pancreas (acini and ducts) except in the Langerhans islets (Figure 3A ) in which orexins could play a role in insulin secretion ( 8 ). This expression in tumoral tissue was independent of patient age, gender, tumor size, and lymph node metastasis ( 46 ). The use of AsPC-1 cell line derived from human PDAC revealed that OxA was able to strongly inhibit cell growth by the SHP2-induced apoptosis ( 46 ).…”
Section: Pancreas Cancermentioning
confidence: 98%
“…This expression in tumoral tissue was independent of patient age, gender, tumor size, and lymph node metastasis ( 46 ). The use of AsPC-1 cell line derived from human PDAC revealed that OxA was able to strongly inhibit cell growth by the SHP2-induced apoptosis ( 46 ). Moreover, the treatment by OxA of tumor slices obtained from patients and maintained in culture, induced the activation of caspases-3 in tumoral tissue demonstrating that OxA was able to induce apoptosis in PDAC ( 46 ).…”
Section: Pancreas Cancermentioning
confidence: 98%
See 3 more Smart Citations